Cytotoxicity and genotoxicity of stilbene derivatives in CHO-K1 and HepG2 cell lines - Mizuno,Cassia Suemi (2017)
Abstract The cytotoxicity and genotoxicity of the stilbenes (E)-methyl-4-(3-5-dimethoxystyryl)benzoate (ester), (E)-4-(3-5-dimethoxystyryl)aniline (amino), (Z)-1,3-dimethoxy-5-(4-methoxystyryl)benzene (cis-TMS) and (E)-1,3-dimethoxy-5-(4-methoxystyryl)benzene (trans-TMS) were investigated in this work. Structural modifications of resveratrol, a naturally occurring stilbene, have been previously performed, including the replacement of hydroxyl by different functional groups. Such modifications resulted in significant improvement of target-specific effects on cell death and antiproliferative responses. The parameters were evaluated using XTT assay, clonogenic survival assay and the cytokinesis-block micronucleus assay in CHO-K1 and HepG2 cell lines. The results showed that cis-TMS is approximately 250-fold more cytotoxic than the amino and ester, and 128-fold more cytotoxic than trans-TMS. When genotoxicity was evaluated, only the trans-TMS did not significantly increase the frequency of micronucleus (MN). While the cis-TMS induced a mean of 5.2 and 5.9 MN/100 cells at 0.5 μM in CHO-K1 and HepG2, respectively, the amino and ester induced 3.1 and 3.6 MN/100 cells at 10 μM in CHO-K1, respectively, and 3.5 and 3.8 in HepG2. Trans-TMS is genotoxic only in HepG2 cells. Based on these results, the cis-TMS was the most cytotoxic and genotoxic compound in both cell lines.